Gastrointestinal Manifestations and Neutrophil-to-Lymphocyte Ratio as Marker of Occult Bleeding in COVID -19 - Maghfirah, Desi; Yusuf, Fauzi; Marisa, Marisa; Eljatin, Muhammad Ridho Akbar (International Journal of Integrated Health Sciences, 2025)
Background: Coronavirus disease 2019 (COVID-19) was initially recognized as a respiratory illness; however, it has been gradually recognized as a disease that affects multiple organ systems, including the gastrointestinal (GI) tract. GI involvement ranges from mild symptoms, such as nausea and diarrhea, to complications like gastrointestinal bleeding. The neutrophil-to-lymphocyte ratio (NLR) has been proposed as a simple biomarker of inflammation and disease severity in COVID-19.Objective: To describe gastrointestinal manifestations of COVID-19 and examine the association between NLR levels and occult gastrointestinal bleeding.Methods: This cross-sectional study was conducted in 2021 at the New-Emerging and Re-Emerging Infectious Diseases inpatient unit of Dr. Zainoel Abidin General Hospital, Banda Aceh, Indonesia. COVID-19-positive patients aged ≥18 years with gastrointestinal symptoms were included, excluding those who were pregnant or had pre-existing GI disorders. Data were collected from medical records and patient interviews. Statistical analysis was performed using the Mann–Whitney U test, with p < 0.05 considered significantResults: The most frequent symptoms were appetite loss and nausea (93%), bloating and vomiting (87%), and diarrhea (57%). Occult GI bleeding occurred in seven patients (23.3%) who had significantly higher NLR values than those without bleeding (p = 0.041).Conclusion: The most frequent GI manifestations of COVID-19 are loss of appetite, nausea, bloating, vomiting, and diarrhea, while occult gastrointestinal bleeding occurs in about one-fourth of cases. Elevated NLR levels are associated with occult bleeding, suggesting its potential role as a simple and accessible biomarker of intestinal inflammation and disease severity.